2019
DOI: 10.1177/0954008318824861
|View full text |Cite
|
Sign up to set email alerts
|

EPDM-based heat-shielding materials modified by hybrid elastomers of silicone or polyphosphazene

Abstract: The erosion resistances of ethylene propylene diene monomer (EPDM) insulations are often inadequate for advanced solid rocket motor (SRM) applications. EPDM modification by blending secondary matrixes is a feasible approach to improve the ablative properties of EPDM insulations. The addition of flexible inorganic hybrid rubbers as a secondary matrix, such as silicones and polyphosphazenes, may impart EPDM insulations with better ablative performance. The blends of EPDM/hybrid rubbers represent the state-of-the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…However, the poor mechanical properties associated with silicones severely restrict their utility [46]. Regarding ablation performance, Wu et al [47] have concluded that with a 1:1 blending ratio of silicone/EPDM, the linear ablation rate was 0.06 mm/s after 20 s of the oxy-acetylene ablation test compared to the much lower result of the EPDM insulation (0.215 mm/s). This result highlights the usefulness of silicone as additive in EHSM formulations.…”
Section: Epdm-based and Nitrile-based Heat Shielding Materialsmentioning
confidence: 99%
“…However, the poor mechanical properties associated with silicones severely restrict their utility [46]. Regarding ablation performance, Wu et al [47] have concluded that with a 1:1 blending ratio of silicone/EPDM, the linear ablation rate was 0.06 mm/s after 20 s of the oxy-acetylene ablation test compared to the much lower result of the EPDM insulation (0.215 mm/s). This result highlights the usefulness of silicone as additive in EHSM formulations.…”
Section: Epdm-based and Nitrile-based Heat Shielding Materialsmentioning
confidence: 99%
“…They show unique advantages in complex deformation and dynamic structure, which can effectively make up for the drawback of rigid insulators. To date, the most widely used elastomeric matrices include nitrile butadiene rubber (NBR), ethylene propylene diene monomer rubber (EPDM), and silicone rubber (SR). , Among them, SR, as an inorganic (semi-organic) material, has received more and more attention due to its excellent oxidation resistance and heat resistance, which is attributed to its special structure with Si–O–Si. Liquid silicone rubber-based ablative materials exhibit great development prospects in thermal protection fields due to their good properties and excellent designability …”
Section: Introductionmentioning
confidence: 99%
“…The PA/PDPP and CF/PDPP composites produced relatively compact charred surface and fewer macro fractures. Remarkably, the charred region of PDPP composites was less prone to expand above the virgin material compared to the conventional fibers reinforced EHSMs 26,36 . This ablation behavior is different from Torre's report on EPDM based EHSMs, where the charred region tends to expand above the virgin material for the EPDM insulations based on different fibrous reinforcements 10,37,38 …”
Section: Resultsmentioning
confidence: 73%
“…Remarkably, the charred region of PDPP composites was less prone to expand above the virgin material compared to the conventional fibers reinforced EHSMs. 26,36 This ablation behavior is different from Torre's report on EPDM based EHSMs, where the charred region tends to expand above the virgin material for the EPDM insulations based on different fibrous reinforcements. 10,37,38 In terms of adhesion of ablative charred layers to the underneath virgin material, PA/PDPP based EHSMs exhibited the best adhesion performance among these different fibrous fillers.…”
Section: Oat Test and Ablative Propertiesmentioning
confidence: 78%